Tukuder Tradition in Jami Al-Muttaqin Mosque Kaliwungu: A Study of Traditional Rites, Culinary Meanings, and its Sustainability - Indra Fibiona; Mawaddatul Khusna Rizqika; Siska Nurazizah Lestari (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
Tukuder tradition in Jami Al-Muttaqin Mosque Kaliwungu is a cultural phenomenon rich in philosophical meanings and implications in the context of local culture. This study aims to investigate the adaptation, philosophical meaning of traditional culinary, and implications of Tukuder Tradition in the lives of Kaliwungu people. Using a qualitative approach, data was obtained through participatory observation, interviews, and document analysis. The results show that Tukuder Tradition has deep roots in the lives of Kaliwungu people and plays an important role in strengthening community identity and togetherness. Traditional culinary such as Telur Mimi, Sumpil, and Momoh, are not just food, but also have a deep philosophical meaning, reflecting the close relationship between humans, nature, and spirituality. The implications of the Tukuder Tradition for the community and local tourism provide inspiration for local economic development and the promotion of sustainable cultural tourism. Therefore, this research makes an important contribution in understanding and appreciating the cultural heritage of the Tukuder Tradition, while stimulating reflection on local identity and wisdom amidst the ever-evolving globalization.